Melasma hyperpigmentation: An overview of current topical therapeutics. Issue 1 (24th August 2022) - AlSalem, Sultan; Alexis, Andrew
Abstract: Background: Melasma is a common disorder of hyperpigmentation that affects populations globally and can adversely affect quality of life. Topical therapies—including hydroquinone and nonhydroquinone‐containing formulations—play a central role in the management of melasma. Methods: A literature review was conducted using PubMed and Google Scholar. Search keywords included a combination of the following: "melasma, " "chloasma, " and "topical treatment." We identified and included seminal and high‐quality peer‐reviewed publications, systematic reviews, randomized controlled trials, case series, case reports, consensus statements, and expert opinions. Results: Topical therapies are widely used for the treatment of melasma. Triple combination cream containing hydroquinone, fluocinolone, and tretinoin is the most studied formulation with the strongest evidence among treatment options. Numerous other prescription‐based and nonprescription topical agents, including a growing list of cosmeceuticals, have been used in the treatment of melasma, albeit in smaller studies. Conclusion: A growing range of topical agents is available for the treatment of melasma. While larger, more robust studies are warranted, nonhydroquinone cosmeceuticals may be useful adjuncts or alternatives to the gold standard of triple‐combination hydroquinone cream.